Integrating Knowledge of Pathology into understanding of Homeopathic Materia Medica (Homoeopathy for All, 2026)
Homeopathy is founded on the principle of "like cures like," and the Materia Medica, which contains detailed descriptions of remedies, helps homeopaths match symptoms of the patient with the most appropriate remedy. Understanding pathology can provide additional insight into how certain remedies interact with disease processes at a deeper level. Here’s how pathology knowledge can contribute to better understanding
Keywords: Materia Medica; Disease Mechanisms; Linking Pathological Changes; Recognizing Disease Progression